Increased Circulatory Extrarenal 1?,25-Dihydroxyvitamin D3 in Bilaterally Nephrectomized Rats - Dabak, Murat; Dabak, Durrin O.; Kuloglu, Tuncay; Baydar, Ersoy; Bulut, Hakan; Ozoner, Ozgur (Bentham Science Publ Ltd, 2020)
Background: Extrarenal 1 alpha,25-dihydroxyvitamin D-3 (1,25-D) locally produced by immune cells plays crucial roles in the regulation of the immune system. However, in vivo status of extrarenal 1,25-D and 25-hydroxyvitamin D (25-D) in acute inflammatory conditions are unknown. Objective: The aim of this study was to determine the extrarenal 1,25-D level in circulation in bilaterally nephrectomized rats, induced by low-dose lipopolysaccharide (LPS). Methods: Renal 1,25-D synthesis was terminated through bilateral nephrectomy in rats. The rats received intraperitoneal LPS (50 mu g/kg BW) three times and the experiment was ended 24 hours after nephrectomy. Serum 1,25-D, 25-D, calcium, phosphorus, intact parathyroid hormone, and calcitonin levels were measured and immunohistochemistry was applied to detect the sources of extrarenal 1,25-D synthesis. Results: Circulatory 1,25-D concentration remarkably increased in both LPS-treated and non-treated bilaterally nephrectomized rats. Elevated circulatory 1,25-D did not have hypercalcemic endocrinal effects. The increased 1,25-D level also resulted in a concurrent rapid and dramatic depletion of circulatory 25-D. Conclusion: Extrarenal 1,25-D could enter into the systemic circulation and, therefore, might have systemic effects besides its autocrine and paracrine functions.
Keywords: 1 alpha,25-dihydroxyvitamin D-3; 25-hydroxyvitamin D; inflammation; extrarenal; anephric; rat